How to Accelerate Corporate and Financial Sector Restructuring in East Asia - Claessens, Stijn (World Bank, Washington, DC, 2012)
Resolving systemic banking and corporate distress is not easy. The large scale of the East Asian financial crisis has made the task even more daunting in Indonesia, the Republic of Korea, Malaysia, and Thailand. Two years into the process, bank and corporate restructuring is still a work in progress. Governments should act to accelerate it. Besides adopting common policy prescriptions - improving financial regulation, corporate governance, and bankruptcy procedures and shoring up banks' capital positions - governments could take three additional steps: Set up competitive, privately managed specialized funds, to hold nonperforming loans and depoliticize restructuring. Allow auctions as an alternative to negotiations, to speed debt restructuring. And allow employee ownership participation schemes, to reduce workers' resistance to changes in ownership.